Assessment of nanoparticles in thermoeconomic improvement of shell and tube heat exchanger. (5th August 2016) - Hajabdollahi, Hassan; Hajabdollahi, Zahra
Highlights: Thermo-economic optimization of a shell and tube heat exchanger by adding Al2 O3 nanoparticles. Effects of nanoparticles on the TAC versus effectiveness at different mass flow rates of tube side. Effects of nanoparticles on tube length, number and pitch ratio versus effectiveness. Variation of objective functions versus volumetric concentration for typical optimum points. Abstract: The influence of nanoparticle Al2 O3 on thermo-economic optimization of a shell and tube heat exchanger (STHE) at different mass flow rates of tube side is explored. Effectiveness and TAC are considered as two objective functions and nine decision variables are selected. The effect of nanoparticle on total annual cost (TAC) versus effectiveness is investigated, which indicates TAC increases by increase of mass flow rate in both cases, however TAC is lower in case with nanoparticles. Furthermore, the effect of nanoparticle on some of heat exchanger specifications is obtained. It shows that STHE needs a lower number of tubes in case with Al2 O3 for a fixed value of effectiveness especially in the lower mass flow rates of tube side. In addition, Al2 O3 does not have the significant effect on the tube length in the fixed value of effectiveness. Furthermore, depending on variations of the pitch and outside diameter of the tube, effectiveness is achieved lower or greater as compared with the base fluid. Finally, the effect of particle volumetric concentration on the objective functions are presented for five typical optimum points. The results show that the effectiveness increases linearly by increase of particle volumetric concentration, while TAC changes nonlinearly.